Is Edema at the Posterior Medial Tibial Plateau Indicative of a Ramp Lesion? An Examination of 307 Patients With Anterior Cruciate Ligament Reconstruction and Medial Meniscal Tears. Issue 6 (27th June 2018) - Kumar, Neil S.; Spencer, Tiahna; Cote, Mark P.; Arciero, Robert A.; Edgar, Cory
Background: Medial meniscal tears are commonly seen during anterior cruciate ligament reconstruction (ACLR). A subset of these injuries includes posterior meniscocapsular junction or "ramp" tears. One criterion that may correlate with a ramp lesion is the presence of posterior medial tibial plateau (PMTP) edema. Purpose: To compare patients with ramp lesions to patients with nonramp (meniscal body) medial meniscal tears and correlate PMTP edema on preoperative magnetic resonance imaging (MRI) to the incidence of ramp tears. Study Design: Case-control study; Level of evidence, 3. Methods: From 2006 to 2016, a total of 852 patients underwent ACLR and had operative reports available for review. Age, sex, laterality, mechanism of injury (contact/noncontact), sport, revision procedure, multiligament injury, time to MRI, and time to surgery were recorded. Preoperative MRI scans were reviewed for PMTP edema using axial, coronal, and sagittal T2 and proton-density sequences. Differences between groups were analyzed using a 2-sample t test and chi-square test. Univariate and multivariate logistic regression models examined correlations with tear type. Results: Overall, 307 patients had medial meniscal tears identified during ACLR (127 ramp lesions, 180 meniscal body lesions). The ramp group was 7.5 years younger than the meniscal body group ( P < .01). The groups were not different regarding sex, contact injury, revision surgery, laterality, or multiligament injury. Patients with delayed ACLR were significantly more likely to have a meniscal body tear than a ramp lesion (odds ratio, 3.3 [95% CI, 1.9-5.6]; P < .01). The sensitivity of PMTP edema for a ramp tear was 66.3%, and 54.5% of patients with ACLR and a medial meniscal tear had PMTP edema. Patients with PMTP edema were significantly more likely to have a ramp tear than a meniscal body tear (odds ratio, 2.1 [95% CI, 1.1-4.1]; P < .03). Conclusion: The overall incidence of ramp tears in patients undergoing ACLR was 14.9%, and these tears were more prevalent in younger patients. Meniscal body tears were significantly more likely than ramp tears with delayed ACLR. In patients undergoing ACLR with an associated medial meniscal tear, the presence of PMTP edema demonstrated significantly greater odds for ramp lesions compared with meniscal body tears.